“Xupa, CAASO!” : masculinidades e relações de gênero na Associação Atlética Acadêmica da UFSCar - Floeter, Guilherme Saade (Universidade Federal de São Carlos, 2012)
This study, done from a ethnographic research (participant observation and interviews) undertaken among undergraduate students of the Federal University of São Carlos (UFSCar), specifically those who participates in the Academic Athletic Association (AAA), presents as main object to analyze how these students show in their practices and discourses within the university environment, the construction of the masculinity(ies) based on gender relations. From the rivalry between UFSCar and USP campus in São Carlos, we try to show how there is a process of gendering and sexualization of both institutions, culminating in the construction of two regulatory poles of gender intelligibility: in one hand, USP, seen as masculine space, because the vast majority of their courses, Engineering, is allocated in the area of Exact Sciences, supposedly more rational and men (heterosexual); and in the other, the UFSCar, university composed of Humanities courses Biological and, in addition to Exact Sciences, and therefore supposed place of women, sensitivity and lack of rationality. Such rivalry, as will be exposed in the text, is not between the two institutions, but among men who are part of them, which shows a continuous process of construction of masculinities, crossed by misogynistic and homophobic speeches, where the constant effort is to reject, deny and ridicule everything that approaches the female pole and homosexuality.
Keywords: Sociologia; Masculinidade; Estudantes universitários; Gênero; Teoria queer; Masculinities; Gender; Undergraduate students; CIENCIAS HUMANAS::SOCIOLOGIA